THE ROLE OF HALAL CERTIFICATION IN BUSINESS PERFORMANCE IN SELANGOR: A STUDY ON KOPITIAMS (Malaysian Management Journal, 2017)
Halal certification plays a key role in food and beverages industry in Malaysia. This certification indicates that the food product is assured in terms of religious compliance, safety and hygiene. There is limited study conducted from the viewpoint of business owners and what benefit it can do in terms of their business development. This research was conducted to associate the role of Halal certification and business performance in four selected Kopitiams around Selangor from various categories; Muslim Halal certified, Muslim not Halal certified, non Muslim Halal certified and non Muslim not Halal certified. Business operators and consumers of the said Kopitiams were interviewed and all case studies were analyzed using descriptive and interpretive analysis. The findings are in line with theories used which are Resource Based View, Theory of Reasoned Action and Theory of Perceived Behavior. The outcome of the study concluded that Halal certificate does bring benefit in their business performance in terms of Islamic view, social contribution, financial capital and human capital. Halal certification is a motivation to gain religious benefit, customer satisfaction, provide more job opportunities and avoid social problems. In financial capital, it serves as an internal resource to boost sales and influence customers’ purchasing decision. For human capital, Halal certificate can increase skill and development of the companies’ human resources.